Heavy Disease Burden of High Systolic Blood Pressure During 1990-2019: Highlighting Regional, Sex, and Age Specific Strategies in Blood Pressure Control - Chen, Ming-Ming; Zhang, Xingyuan; Liu, Ye-Mao; Chen, Ze; Li, Haomiao; Lei, Fang; Qin, Juan-Juan; Ji, Yanxiao; Zhang, Peng; Cai, Jingjing; She, Zhi-Gang; Zhang, Xiao-Jing; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: High systolic blood pressure (HSBP) remains the leading risk factor for mortality worldwide; however, limited data have revealed all-cause and cause-specific burdens attributed to HSBP at global and regional levels. This study aimed to estimate the global burden and priority diseases attributable to HSBP by region, sex, and age. Methods: Based on data and evaluation methods from the Global Burden of Diseases, Injuries, and Risk Factors Study 2019, we estimated trends of age-standardized mortality rate (ASMR), age-standardized rate of disability-adjusted life years (ASDRs), and age-standardized rate of years lived with disability (ASYRs) attributable to HSBP during 1990-2019. Further, we analysed cause-specific burdens attributable to HSBP by sex, age, year, and region. Results: Globally, a significant downtrend was found in the ASMR attributed to HSBP while ASYRs did not change substantially during 1990-2019. The majority of HSBP burden has shifted from high-middle sociodemographic index (SDI) regions to lower SDI regions. All-cause and most cause-specific burdens related to HSBP were improved in high SDI regions but the downtrends have stagnated in recent years. Although many cause-specific deaths associated with HSBP declined, chronic kidney disease (CKD) and endocarditis associated deaths were aggravated globally and ischemic heart disease (IHD), atrial fibrillation and flutter, aortic aneurysm (AA), and peripheral artery disease (PAD) associated deaths were on the raise in low/low-middle/middle SDI regions. Additionally, males had higher disease burdens than females. Middle-aged people with CVDs composed the major subgroup affected by HSBP while older people had the highest ASMRs associated with HSBP. Conclusions: This study revealed the global burden and priority diseases attributable to HSBP with wide variation by region, sex, and age, calling for effective and targeted strategies to reduce the prevalence and mortality of HSBP, especially in low/low-middle/middle SDI regions.